(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper presents an Iberian graffito datable back to the early 1st century BC and retrieved at the archaeological works developed at the baths of La Cabañeta (El Burgo de Ebro, Zaragoza), a Roman site from the Republican period. New information about Iberian writing and language is given in this document, as well as an unprecedented personal name and a likely verbal form. It also shows the continuance of dual writing system graphic forms in later texts written in non-dual writing system.